2020
DOI: 10.3847/1538-4357/abbacc
|View full text |Cite
|
Sign up to set email alerts
|

The Lyα Emission in Solar Flares. I. A Statistical Study on Its Relationship with the 1–8 Å Soft X-Ray Emission

Abstract: We statistically study the relationship between the Lyα and 1–8 Å soft X-ray (SXR) emissions from 658 M- and X-class solar flares observed by the Geostationary Operational Environmental Satellite during 2006–2016. Based on the peak times of the two wave band emissions, we divide the flares into three types. Type I (III) has an earlier (a later) peak time in the Lyα emission than that in the SXR emission, while type II has nearly the same peak time (within the time resolution of 10 s) between the Lyα and SXR em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 56 publications
0
16
3
Order By: Relevance
“…These could be accompanied by some plasma motions such as chromospheric evaporation and coronal condensation, which have different directions along the loops. Compared with previous studies on flaring Lyα (e.g., Nusinov et al 2006;Rubio da Costa et al 2009;Jing et al 2020), our study provides a direct imaging evidence for the Lyα emission originating from flare ribbons as well as flare loops for the first time. In addition, the thermal origin of Lyα is supposed to be more important than the nonthermal origin in this small flare, which may be different with the case in large or major flares.…”
Section: Physical Origin Of the Flaring Lyα Emissionmentioning
confidence: 57%
See 1 more Smart Citation
“…These could be accompanied by some plasma motions such as chromospheric evaporation and coronal condensation, which have different directions along the loops. Compared with previous studies on flaring Lyα (e.g., Nusinov et al 2006;Rubio da Costa et al 2009;Jing et al 2020), our study provides a direct imaging evidence for the Lyα emission originating from flare ribbons as well as flare loops for the first time. In addition, the thermal origin of Lyα is supposed to be more important than the nonthermal origin in this small flare, which may be different with the case in large or major flares.…”
Section: Physical Origin Of the Flaring Lyα Emissionmentioning
confidence: 57%
“…This Neupert effect (Neupert 1968) was also detected in some other flares for Lyα (e.g., Rubio da Costa et al 2009;Milligan & Chamberlin 2016;Milligan et al 2017;Chamberlin et al 2018;Dominique et al 2018;Wauters et al 2022). Interestingly, Jing et al (2020) studied 658 M-and X-class flares and found that in ∼20% of the events the Lyα peak appears later than the SXR peak. This delayed Lyα emission can mostly be contributed by thermal plasmas that cool down, suggesting a thermal origin.…”
Section: Introductionmentioning
confidence: 65%
“…The hydrogen Balmer continuum enhancement at MUV wavelengths around 2000 Å was found to be highly synchronous with the enhancement of Lyα emission during a powerful solar flare (Dominique et al 2018), while the flare radiation in the Lyα and HXR ranges were demonstrated to have a close relationship (Nusinov et al 2006;Jing et al 2020;Lu et al 2021b). However, flarerelated QPPs were rarely observed simultaneously in these channels.…”
Section: Introductionmentioning
confidence: 90%
“…A value of E FP /E IP 2 implies at least half of the total energy radiated during the flare is radiated after the impulsive phase, as was the case for SOL2011-09-24 and SOL2014-02-01. Possible contributions to the elevated flux may be attributed to evaporated material in the corona cooling to chromospheric temperatures (Jing et al 2020), failed filament eruptions (Wauters et al 2022), or evaporated material driven by thermal conduction (Zarro & Lemen 1988), for example. While we cannot necessarily determine the source of the emission using disk-integrated measurements alone, nonchromospheric contributions should not be neglected from the interpretation of the results presented here.…”
Section: Energeticsmentioning
confidence: 99%